The JCT 2011 building sub-contracts - Barnes, Peter, 1954-; Davies, Matthew, 1970- (Chichester, West Sussex : John Wiley & Sons Inc., 2015)
"Covers key contract conditions, rights and obligations, and risk under the JCT 2011 Building Sub-contracts"--
Background and introduction -- The sub-contract agreement -- Definitions and interpretations -- Sub-contractors : general obligations -- Time -- Defects, design documents and warranties -- Control of the sub-contract works -- Payment -- Loss and expense -- Variations -- Injury, damage and insurance -- Termination of sub-contract -- Settlement of disputes.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Joint Contracts Tribunal; Joint Contracts Tribunal; Construction contracts -- Great Britain; Construction industry -- Subcontracting -- Great Britain; LAW -- Construction; Construction contracts; Construction industry -- Subcontracting; Great Britain; Electronic books